Minimizing Warehouse Space through Inventory Reduction at Reckitt Benckiser - KILINC, IZGI SELEN (2009)
This dissertation represents a ten week internship at pharmaceutical plant of Reckitt Benckiser for the Warehouse Stock Reduction Project. Due to foreseeable growth by the factory, there is increasing pressure to utilise existing warehouse space by reducing the existing stock level by 50 %. Therefore, this study aims to identify the opportunities to reduce the physical stock held in raw/pack materials in the warehouse and save space for additional manufacturing resources. The analysis demonstrates the reasons for high stock levels in the warehouse, and the problems with the current system, inventory management and material flow. Moreover, ABC analysis identifies relevant categories of materials and suppliers to find optimum ways of supplier replenishment to minimize the physical stock. Based on the analysis and findings, this study represents the opportunities that could lead stock reduction in raw/pack materials warehouse. Proposed solutions are focused on four main parts: Obsolete stock management, replenishment methods and JIT supply, warehouse configurations for space saving, and long term solutions such as VMI, SAP and information sharing. This study concludes with a general guideline for companies to reduce the stock levels for incoming materials, to better manage the inventory and save warehouse space without compromising the warehouse operational efficiency and company’s benefits.